Soil quality in olive orchards of southern Peru using a weighted soil quality index (SQIw): constraints by salinity, organic matter and sustainable management approach - Poma-Chamana, Russell; Vilca-Gamarra, Cesar; Linares-Escapa, Solmayra; Puma-Huacani, Katherine; Carrillo, Alex; Villalta Soto, Martín J. C.; Quispe, Kenyi (Frontiers in Soil Science, 2026)
IntroductionSoil salinization and alkalinization in the arid zones of southern Peru pose major challenges to agricultural sustainability, particularly in the olive orchards of Bella Unión, where irrigation relies on surface and groundwater of variable quality. This study aimed to assess soil quality and its spatial variability to support site-specific management in olive (Olea europaea L L.) orchards.MethodsA total of 160 composite soil samples (0–30 cm) were collected from representative olive orchards and analyzed for pH, electrical conductivity (ECe), organic matter (OM), available phosphorus (Pav), available potassium (Kav), texture, and calcium carbonate equivalent (CCE). The Soil Quality Index (SQIw) was calculated and combined with multivariate and geostatistical analyses to identify key soil quality indicators and characterize their spatial variability.ResultsSoils showed high variability in salinity (ECe = 1.30–24.61 dS m-¹) and organic matter content (0.50–3.10%), while pH was relatively homogeneous (6.90–8.40). According to the SQIw, 1.26% of soils were classified as Very Poor, 44.96% as Poor, 51.49% as Acceptable, 2.28% as Good, and 0.01% as Optimal. Electrical conductivity was the main factor controlling the SQIw.DiscussionThese results indicate that salinity represents a major constraint for olive growth and productivity in the study area. Despite its lower weight in the SQIw, the generally low organic matter levels suggest limitations for soil fertility, water retention, and nutrient cycling, highlighting the need for organic amendments with low electrical conductivity. Nutrient management should also account for reduced nutrient availability under alkaline–saline conditions and the widespread organic matter deficiency. This study represents the first application of SQIw in Peruvian olive orchards and demonstrates its usefulness for delineating low-quality zones, guiding fertilization and soil recovery strategies, and promoting sustainable soil management in arid agroecosystems.